2011
DOI: 10.1902/jop.2010.100319
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Stress Markers, Stress, and Periodontitis: A Pilot Study

Abstract: This study suggests that stress might be associated with periodontal disease through physiologic and behavioral mechanisms. In making diagnoses of psychiatric patients, the association between salivary stress markers and periodontal disease needs to be included. Further exploration of relationships between periodontitis and stress is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
89
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 25 publications
4
89
0
5
Order By: Relevance
“…Stress is an important risk factor in periodontitis, as shown in our previous studies (15)(16)(17). Stress is induced in an isolated environment and in an international, multicultural work atmosphere (16)(17)(18)(19); however, the harsh environment might have caused stress during this mission. Decreases in immunoglobulin levels might have been due to compromised mucosal immunity (20).…”
Section: Discussionmentioning
confidence: 72%
“…Stress is an important risk factor in periodontitis, as shown in our previous studies (15)(16)(17). Stress is induced in an isolated environment and in an international, multicultural work atmosphere (16)(17)(18)(19); however, the harsh environment might have caused stress during this mission. Decreases in immunoglobulin levels might have been due to compromised mucosal immunity (20).…”
Section: Discussionmentioning
confidence: 72%
“…In general, the analysis of the studies revealed a positive association between stress and periodontal disease. Unlike the previous review by Peruzzo et al [9], we identified one cohort study [41] that suggested persuasive evidence of psychological distress and social support as risk factors.The positive association was derived predominantly from prospective clinical trial [42], cross-sectional [16,17,[28][29][30][31]33,37] and case-control studies [38][39][40]. One crosssectional study by Forte et al [32] did not reproduce a positive finding.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve studies were cross-sectional [16,17,[28][29][30][31][32][33][34][35][36][37], three were casecontrol [38][39][40] studies, one was a cohort study [41] and two were prospective clinical trial [4,42] studies, comprising 5051 individuals. Two of the studies were conducted only with women [16,34], and two studies did not mention the gender distribution [29,31].…”
Section: Description Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduction of salivary flow may also occur because of stress [21]. Rai et al observed a positive association between the stress score and salivary stress markers, such as cortisol [33]. The depressed individuals showed higher concentrations of cortisol in the gingival fluid, responding in an inadequate way to the treatment for periodontal disease.…”
Section: Risk Factors Associated To Periodontal Diseasementioning
confidence: 99%